Strategi Kebijakan Pengembangan Kepariwisataan: Mewujudkan Pariwisata Berkelanjutan dan Inklusif di Indonesia - Erina Kusumawati; Afrian Tito Setyawan; Julfa Luthfiya Fitri; Rona Martilisa; Miftakhul Asna; Siti Nur Laili; Bagus Setiawan (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2026)
Sustainable and inclusive tourism represents a key policy direction in Indonesia's national development agenda, aiming to balance economic growth with environmental preservation and social equity. This study explores policy strategies that promote sustainable and inclusive tourism development through a qualitative approach, combining case studies and literature review. Case studies were conducted on two destinations: Nglanggeran Tourism Village in Yogyakarta and Komodo National Park in East Nusa Tenggara, both of which exemplify effective integration of sustainability principles. The literature review examined relevant theories, policy frameworks, and best practices from scholarly sources and official documents. Data were analyzed using content analysis to identify key themes and strategic patterns. The findings reveal that effective policy strategies emphasize community empowerment, multi-stakeholder collaboration, local resource-based planning, and institutional strengthening. The study recommends adaptive and participatory policy frameworks that embed local contexts and community roles at the core of sustainable tourism development in Indonesia. Keywords: sustainable tourism, inclusive development, tourism policy